Analisis Sentimen Konten Radikal Melalui Dokumen Twitter Menggunakan Metode Backpropagation - Brian Andrianto; Indriati Indriati; Sigit Adinugroho (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Twitter is a social networking service where users can post and interact with messages, known as "tweets". Twitter is also used by some people to give their opinions on something but sometimes too excessive even sometimes found a tweet that smells radical. The radical actions that exist in social media are usually referred to as radical content. The radical content available on social media can certainly harm some parties. There are also certain parties who utilize radical content to achieve certain goals. Therefore, in this study try to analyze the Indonesian tweet that contains the word radical, including in the content of radical positive or negative radical. Tweet can be from twitter that contains public opinion that leads to radical content will be classified. Tweet can be called a document or data will first go through the preprocessing process. Then the document was broken into 6 types of words, including the nouns, verbs and adjectives where each type of word will be divided again into positive and negative. After the break will be calculated how many the number of types of words in each document so that it can be converted into numbers that can then be incorporated into the algorithm formula.